2018
DOI: 10.1111/eva.12725
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of fitness and demographic effects of a Chinook Salmon supplementation program

Abstract: While the goal of supplementation programs is to provide positive, population‐level effects for species of conservation concern, these programs can also present an inherent fitness risk when captive‐born individuals are fully integrated into the natural population. In order to evaluate the long‐term effects of a supplementation program and estimate the demographic and phenotypic factors influencing the fitness of a threatened population of Chinook Salmon ( Oncorhynchus tshawytscha ), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(121 citation statements)
references
References 80 publications
(151 reference statements)
4
113
0
Order By: Relevance
“…Flow cytometry analysis of 100 individuals produced using this method demonstrated that all 100 were triploid (P. Branigan, unpublished data). GT‐seq was used to genotype these samples for a panel of 298 SNPs (Janowitz‐Koch et al, ). The loci in this panel have median and mean ± SD mean read depths around 140 and 225 ± 270 reads per individual, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry analysis of 100 individuals produced using this method demonstrated that all 100 were triploid (P. Branigan, unpublished data). GT‐seq was used to genotype these samples for a panel of 298 SNPs (Janowitz‐Koch et al, ). The loci in this panel have median and mean ± SD mean read depths around 140 and 225 ± 270 reads per individual, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…; Janowitz‐Koch et al. ). In the Pacific Northwest, supplementation is a principal strategy that is intended to mitigate the effects on Pacific Salmon Onchorynchus spp.…”
mentioning
confidence: 99%
“…Adopting such an approach for the Hunder trout would be beneficial for quantifying past and future impact of stocking on genetic variation. It could also aid in developing strategies for enhancing stocking practices to minimise negative genetic and demographic impacts (Araki & Schmid 2010) and for weighing different stocking practices against compensatory mitigation measures (Johnston et al 2018, Arlinghaus et al 2002, Janowitz-Koch et al 2018.…”
Section: Discussionmentioning
confidence: 99%